POLITIK HUKUM PERLINDUNGAN DATA PRIBADI DALAM UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Jannah, Illa Miftahul (Universitas Nurul Jadid, 2024)
The development and advancement of technology brings about changes in people's lives that give rise to legal actions. In line with this, in anticipation of unlawful acts, namely misuse of personal data in obtaining information and conducting electronic transactions, it must provide protection of personal data with the need for legal products in order to strengthen protection and can provide security and protection of everyone's personal data. Therefore, the existence of Law No. 19 of 2016 on ITE should be in accordance with the expectations of Indonesian citizens, namely to provide guarantees of security and legal certainty with regard to the protection of personal data and in accordance with the criteria and political objectives of the law.